Mortal Kombat legends : battle of the realms [videorecording (Blu-Ray)] - Adams, Jeremy (Screenwriter) (Warner Bros. Entertainment, 2021)
After the events of the first Mortal Kombat tournament, Liu Knag, Raiden, Johnny Cage, Sonya Blade, and Jack Briggs return home to find EarthRealm invaded by the forces of Outworld. The evil warlord Shao Kahn presents the heroes with an ultimatum; agree to a new Mortal Kombat tournament or face an all-out war with Outworld. Now the heroes, along with new allies Kung Lao and Stryker, must journey to Outworld and fight for the survival of Earthrealm in the tournament to end all tournaments.